A systematic literature review on analysis of optimal location for crop farming - Muhammad Yusuf Idris; Zurinah Tahir (Penerbit Universiti Kebangsaan Malaysia, 2025)
Crop farming, crucial for global food security, faces challenges like climate change, soil degradation, and resource scarcity. This systematic literature review (SLR) investigated methodologies and technologies for determining optimal crop farming locations, focusing on the integration of Geographic Information Systems (GIS) analysis, Remote Sensing, and Multi-Criteria Decision Analysis (MCDA), particularly the Analytical Hierarchy Process (AHP). The objective was to synthesize findings from peer-reviewed studies to understand how these technologies contribute to sustainable agricultural practices and address global food security challenges. The SLR followed the PRISMA protocol, analyzing data from 69 peer-reviewed studies. Findings highlighted GIS and Remote Sensing as pivotal tools for spatial mapping, land suitability assessment, and real-time monitoring, while MCDA and AHP were instrumental in evaluating multi-dimensional criteria. The analysis explored the strengths and weaknesses of various methodologies and their applications in diverse geographical regions and farming systems. Implications suggest that integrating geospatial technologies and decision-making frameworks is critical for promoting sustainable agricultural practices and addressing global food security challenges. Further research is needed to explore the influence of social and cultural factors on location decisions and to further integrate advanced technologies for diverse contexts.